Prevalence and Molecular Identification of Entamoeba spp. in Non-human Primates in a Zoological Garden in Nanjing, China - Liu, Xinchao; Bao, Guangbin; Yue, Menglong; Fang, Yi; Gu, Yueyue; Li, Wenchao; Gu, Youfang; Cheng, Wangkun; Lu, Mingmin (Frontiers in Veterinary Science, 2022)
Objective: Entamoeba spp. are globally distributed zoonotic parasites that infect various hosts, among which non-human primates (NHPs) have been identified as one of the most common hosts of these parasites. Consequently, the infections of Entamoeba spp. in captive NHPs from Nanjing Hongshan Forest Zoo in China were investigated in order to assess their zoonotic potential. Methods: A total of 120 fresh fecal samples, including 19 species of NHPs, were collected from four breeding bases of the zoo from May to June 2019. The infections of six species of Entamoeba spp. were detected by PCR using the 16S or 18S rDNA-specific primers, and the positive samples were sequenced and analyzed. Results: Entamoeba spp. were detected as positive in 59 NHPs fecal samples (49.17%), including five Entamoeba species: Entamoeba histolytica (7.50%), E. dispar (22.50%), E. coli (22.50%), E. chattoni (10.00%) and E. nuttalli (1.67%). Infection with one Entamoeba species was more common (35%) than co-infections (13.33%) or infections with three Entamoeba species (0.83%). There was a significantly higher prevalence rate of Entamoeba spp. in the species Pongo pygmaeus and Macaca mulatta than in Papio sp., Mandrillus sphinx, and Saimiri sciureus. Conclusion: Entamoeba spp. are highly prevalent in the NHPs raised in Nanjing Hongshan Forest Zoo. Therefore, attention should be paid to the development of containment strategies of Entamoeba spp. in this zoological garden.